Magneto-dielectric and multiferroic properties in Bi0.95Yb0.05Fe0.95Co0.05O3. (2nd April 2019) - Singh, Gulab; Bhasker, H P; Yadav, R P; Kumar, Aditya; Khan, Bushra; Kumar, Ashok; Singh, Manoj K
Abstract: Bismuth ferrite (BFO) and (Yb, Co) co-doped BFO powder are successfully synthesized using the sol-gel method. The structural, electrical, magneto-dielectric and multiferroic properties of pure and co-doped BFO have been systematically investigated. The crystal structures of these samples are investigated using x-ray diffraction techniques, which confirmed the single-phase polycrystalline rhombohedral perovskite structure with the R3c space group. The co-substitution studies revealed that the electrical, ferromagnetic and ferroelectric properties of BFO were significantly enhanced compared to pure BFO samples.